Impact of Inflammatory Cytokines on Effector and Memory CD8+ T Cells - Kim, Marie T.; Harty, John T. (Frontiers in Immunology, 2014)
Inflammatory cytokines have long been recognized to produce potent APCs to elicit robust T cell responses for protective immunity. The impact of inflammatory cytokine signaling directly on T cells, however, has only recently been appreciated. Although much remains to be learned, the CD8 T cell field has made considerable strides in understanding the effects of inflammatory cytokines throughout the CD8 T cell response. Key findings first identified IL-12 and type I interferons as ‘signal 3’ cytokines, emphasizing their importance in generating optimal CD8 T cell responses. Separate investigations revealed another inflammatory cytokine, IL-15, to play a critical role in memory CD8 T cell maintenance. These early studies highlighted potential regulators of CD8 T cells, but were unable to provide mechanistic insight into how these inflammatory cytokines enhanced CD8 T cell-mediated immunity. Here, we describe the mechanistic advances that have been made in our lab regarding the role of ‘signal 3’ cytokines and IL-15 in optimizing effector and memory CD8 T cell number and function. Furthermore, we assess initial progress on the role of cytokines, such as TGF-β, in generation of recently described resident memory CD8 T cell populations.